Assessing Refugees’, asylum seekers’ and vulnerable migrants’ soft skills: The development and psychometric properties of NADINE Soft Skills Test - Tountopoulou, Maria; Drosos, Nikos; Vlachaki, Fotini (Advances in Social Sciences Research Journal, 2021)
This paper aims to give an overview of the development of the NADINE soft skills test, focusing mainly on the results of the study conducted to assess the psychometric properties of it, so as to ensure that the proposed test is suitable, reliable and valid to assess the soft skills of migrant groups. The sample used for the standardization of the tools consisted of 427 persons. Reliability and validity of tools were calculated; factor analyses were conducted to ensure that each scale was measuring only one factor and further comparative analyses were made to explore whether there is statistical significant relation between demographic variables and the performance in the skills under evaluation. Results of the analyses depict that the NADINE soft skill test constitute valid and reliable instrument that can be used by career practitioners, hosting organisations and administration bodies to accurately assess the soft skills of vulnerable migrants, refugees and asylum seekers and facilitate their labour market integration.